Hubungan Self Efficacy dengan Self Care Management Lansia yang Menderita Hipertensi di Posyandu Lansia Padukuhan Panggang III Binaan Puskesmas Panggang I Gunungkidul - Andri Setyorini (STIKes Surya Global Yogyakarta, 2018)
One of the health problems that often occured in the elderly is cardiovascular system one of them is hypertension. Hypertension is estimated to cause 7.5 million deaths, about 12.8% of the total of all deaths. The incidence of hypertension increase each year and the problem that often occurs in hypertensive patients are non-adherence to therapy or treatment, lifestyle changes and complications due to hypertension. This cases are influenced by self efficacy that the elderly have to change the behavior of self-care is less good. This research is aimed to know the correlation between self efficacy and hypertension self-care management among Elderly In Elderly Integrated Service Centre Panggang III at Panggang I Community Health Centre Gunungkidul. This research design was descriptive correlational with cross sectional approach. There was 25 elderly who have hypertension and they take a part Posyandu Lansia Activity. The data has been analyzed using Spearman Rank. This research showed that the elderly who have hypertension at Elderly Integrated Service Centre Panggang III have a bad category of self efficacy about 21 elderly (84%) and have a bad category of self care management about 16 elderly (64%). This research also showed that there was a significant correlation between self efficacy and self care management with score ρ=0.002 α=0.05. There was a correlation between self efficacy and hypertension self-care management among Elderly In Elderly Integrated Service Centre Panggang III at Panggang I Community Health Centre Gunungkidul.